Using the notations from Backpropagation calculus | Deep learning, chapter 4, I have this back-propagation code for a 4-layer (i.e. 2 hidden layers) neural network:
def sigmoid_prime(z):
return z * (1-z) # because σ'(x) = σ(x) (1 - σ(x))
def train(self, input_vector, target_vector):
a = np.array(input_vector, ndmin=2).T
y = np.array(target_vector, ndmin=2).T
# forward
A = [a]
for k in range(3):
a = sigmoid(np.dot(self.weights[k], a)) # zero bias here just for simplicity
A.append(a)
# Now A has 4 elements: the input vector + the 3 outputs vectors
# back-propagation
delta = a - y
for k in [2, 1, 0]:
tmp = delta * sigmoid_prime(A[k+1])
delta = np.dot(self.weights[k].T, tmp) # (1) <---- HERE
self.weights[k] -= self.learning_rate * np.dot(tmp, A[k].T)
It works, but:
the accuracy at the end (for my use case: MNIST digit recognition) is just ok, but not very good. It is much better (i.e. the convergence is much better) when the line (1) is replaced by:
delta = np.dot(self.weights[k].T, delta) # (2)
the code from Machine Learning with Python: Training and Testing the Neural Network with MNIST data set also suggests:
delta = np.dot(self.weights[k].T, delta)
instead of:
delta = np.dot(self.weights[k].T, tmp)
(With the notations of this article, it is:
output_errors = np.dot(self.weights_matrices[layer_index-1].T, output_errors)
)
These 2 arguments seem to be concordant: code (2) is better than code (1).
However, the math seem to show the contrary (see video here; another detail: note that my loss function is multiplied by 1/2 whereas it's not on the video):
Question: which one is correct: the implementation (1) or (2)?
In LaTeX:
$$\frac{\partial{C}}{\partial{w^{L-1}}} = \frac{\partial{z^{L-1}}}{\partial{w^{L-1}}} \frac{\partial{a^{L-1}}}{\partial{z^{L-1}}} \frac{\partial{C}}{\partial{a^{L-1}}}=a^{L-2} \sigma'(z^{L-1}) \times w^L \sigma'(z^L)(a^L-y) $$
$$\frac{\partial{C}}{\partial{w^L}} = \frac{\partial{z^L}}{\partial{w^L}} \frac{\partial{a^L}}{\partial{z^L}} \frac{\partial{C}}{\partial{a^L}}=a^{L-1} \sigma'(z^L)(a^L-y)$$
$$\frac{\partial{C}}{\partial{a^{L-1}}} = \frac{\partial{z^L}}{\partial{a^{L-1}}} \frac{\partial{a^L}}{\partial{z^L}} \frac{\partial{C}}{\partial{a^L}}=w^L \sigma'(z^L)(a^L-y)$$